PENGARUH NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN SPRING BED MEREK COMFORTA DI KOTA PALU - AVRIANI, PUTRI DWI (Fakultas Ekonomi Universitas Tadulako, 2016)
This research aims to know the effect of customer value while simultan and partially on customersatisfaction by using spring bed of Comforta In the Palu City. The independent variables used in thisresearch are Functional Value (X1), Value For Money (X2), Social Value (X3), and Emotional Value(X4). While the dependent variable is Satisfaction (Y). The research method used in this research isdescriptive causal. Sampling technique using Insidential sampling with the samples of 100respondents. The method analysis using multiple linear regression. The results indicate thatsimultaneously customer value consisting of functional value (X1), value for money (X2), social value(X3) and emotional value (X4) have significant effect to customer satisfaction by using Spring Bed ofComforta in Palu City. The Partially customer value consisting of functional value (X1), value formoney (X2), and emotional value (X4) have significant effect to customer satisfaction by using springbed of Comforta in Palu City. While variable social value (X3) partially have no significant effect oncustomer satisfaction by using spring bed of Comforta in Palu City.